THE POLITICAL THOUGHT OF RASHIDUN CALIPHATE - Wahyuniar WN; Nur Afifa (Jurnal Al-Dustur, 2020)
This study examines the political thought of the era of khulafa' al-rasyidin. The aim is to explain the differences in political practices in each caliph reign after the death of the Prophet. Political practices have been carried out since the time of the Prophet Muhammad which is the Medina period, where the Prophet served as religious leader as well as head of state. During this time, the Prophet has many companions who were strong and smart in political affairs. After the death of the Prophet Muhammad the reign is successed by the sahabah or the companions. Historically, Muslims has four companions who are the successor to the Prophet, known as Khulafa' al-rasyidin. The political practice is adopted by Khulafa 'al-Rashidin has a standardized system, each caliph who rules implementing a different political system, following the conditions of the people that occurred at era. The four caliphs are appointed as leaders in different ways.